2004
DOI: 10.1111/j.1469-8137.2004.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Thlaspi caerulescens on nonmetalliferous soil in Luxembourg: ecological niche and genetic variation in mineral element composition

Abstract: Summary• Forty-seven populations of Thlaspi caerulescens in Luxembourg were characterised for population size, soil mineral element composition and other habitat characteristics. Foliar concentrations of eight elements were assessed in 15 populations in the field and in eight populations cultivated in zinc (Zn)-cadmium (Cd)-nickel (Ni)-enriched soil.• T. caerulescens favoured stony soil developed on steep, south-facing Emsian shale outcrops. All soil samples were nonmetalliferous. Soil pH ranged from 4.2 to 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
(38 reference statements)
5
35
2
Order By: Relevance
“…caerulescens (Brassicaceae, formerly Thlaspi caerulescens) is one of the most promising candidate species for Cd and Zn phytoextraction (Koopmans et al 2008;Maxted et al 2007;McGrath et al 2006;Zhao et al 2003). Three ecotypes of N. caerulescens have been described: metallicolous plants grow in soils enriched in Cd-Zn-Pb (calamine, CAL) and in serpentine sites (mostly enriched in Ni), whereas non-metallicolous (NMET) grow in uncontaminated soils (Escarré et al 2000;Meerts and van Isacker 1997;Molitor et al 2005;Reeves et al 2001). CAL and NMET ecotypes have different metal-related traits.…”
Section: Responsible Editor: Elena Maestrimentioning
confidence: 99%
See 2 more Smart Citations
“…caerulescens (Brassicaceae, formerly Thlaspi caerulescens) is one of the most promising candidate species for Cd and Zn phytoextraction (Koopmans et al 2008;Maxted et al 2007;McGrath et al 2006;Zhao et al 2003). Three ecotypes of N. caerulescens have been described: metallicolous plants grow in soils enriched in Cd-Zn-Pb (calamine, CAL) and in serpentine sites (mostly enriched in Ni), whereas non-metallicolous (NMET) grow in uncontaminated soils (Escarré et al 2000;Meerts and van Isacker 1997;Molitor et al 2005;Reeves et al 2001). CAL and NMET ecotypes have different metal-related traits.…”
Section: Responsible Editor: Elena Maestrimentioning
confidence: 99%
“…Experimental design and plant cultivation N. caerulescens seeds came from three populations: two NMET from the Grand Duchy of Luxemburg, Wilwerwiltz and Goebelsmühle (hereafter WIL and GOE) (Molitor et al 2005), and one metallicolous Ganges (GAN, or BAvinières^) from St-Laurent-le-Minier, France (Escarré et al 2000). Seedlings of N. caerulescens were grown in greenhouse for 2.5 months before transplanting in the field.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 9 NMET soils in Switzerland (<120 mg/kg of Zn in soil), Zn leaf concentrations values averaged 4857 mg/kg (Basic et al 2006), and in 15 NMET populations from Luxembourg (soil=8.6 mg/kg Zn) mean Zn leaf values were 7300 mg/kg (Molitor et al 2005). Banásová et al (2008) found mean Zn concentrations of 13650 mg/kg and of 10729 mg/kg in MET and NMET populations, respectively, in central Slovakia.…”
Section: Zinc Concentration and Zinc Massmentioning
confidence: 99%
“…In each population, seeds from 20-30 flowering plants were collected. To analyse the extractable Zn, Cd, Pb and Ni concentrations of soil, bulk samples were air-dried, ground and the <2 mm fractions were separated from coarse rock (Frérot et al 2006) Total Zn 126126±17620 mg/kg; total Cd 899±200 n=3 (Escarré et al 2011) b (Dechamps et al 2008a,b;Molitor et al 2005) c Total Zn concentration (Reeves et al 2001) d Total Ni concentration: 146 to 2500 mg/kg (Chardot et al 2007) e Total Ni concentration:784-1984 mg/kg (Reeves et al 2001) fragments by sieving. All chemical analyses were performed on the <2 mm soil fractions.…”
Section: Plant and Soil Materialsmentioning
confidence: 99%